Buddhism and Spinoza on the three kinds of knowledge. Issue 2 (3rd April 2023) - Hongladarom, Soraj
ABSTRACT: The conceptions of three kinds of knowledge in Buddhism and in Spinoza are compared. There are both similarities and differences in the two conceptions, both of which provide interesting insights into both traditions. The similarities are that the three kinds of knowledge represent a hierarchical structure, starting from the first kind, characterized by sense perception. The second kind for Spinoza is characterized by rational knowledge, which is comparable to the Buddhist second kind, which is about thinking through what one has heard. These two kinds lead to the third kind of knowledge, which in Spinoza is intuitive knowledge, and in Buddhism is knowledge by mental cultivation. In both traditions, these three kinds of knowledge lead to soteriological aims. Among the differences is that Spinoza presents his three kinds of knowledge through a series of axioms and proofs, whereas in Buddhism they form a guideline for the practitioner.